Biogenic synthesis and characterization of AgNPs Using CEPS: cytotoxicity and antibacterial activites - Ismail Zainol (Tanjung Malim, 2023)
Biogenic synthesis and characterization of AgNPs Using CEPS: cytotoxicity and antibacterial activites by Ismail Zainol